Does diversification increase or decrease bank risk and performance? Evidence on diversification and the risk-return tradeoff in banking - Allen N. Berger; Iftekhar Hasan; Iikka Korhonen; Mingming Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
Conventional wisdom in banking argues that diversification tends to reduce bank risk and improve performance, but the recent financial crisis suggests that aggressive diversification strategies may have resulted in increased risk taking and poor performance. This paper addresses this important question by evaluating the empirical relationship between diversification strategies and the risk-return tradeoff in banking. Our data set covers Russian banks during the 1999-2006 period and finds somewhat mixed results. Specifically, we find that banks performance tends to be non-monotonically related to their diversification strategy. The marginal effects of focus indices (inverse measures of diversification) on performance are nonlinearly associated with the level of risk and foreign ownership. A focused strategy is found to be associated with increased profit and decreased risk only up to a certain threshold. Additionally, when foreign ownership is either very high or very low, banks tend to benefit more from being diversified. This analysis provides important strategic and policy implications for bank managers and regulators in Russia as well as in other emerging economies.
URN:NBN:fi:bof-201408071987
Keywords: 330